EFFECTIVENESS OF THE RESOTTA STONE APP FOR ENGLISH PRONUNCIATION SKILLS: English - Nurhijriah; Hardianti; Lailatul Islami, Dhiya; Maryam Hamid, Sitti (EDUCATE : Journal of Education and Culture, 2025)
Learning media is a form of learning that can present learning materials in a contextual, audio and visual way in an interesting and interactive way. One example of such learning media is the use of the Rosetta Stone application. Rosetta Stone is a language learning app that uses voice recognition and dynamic immersion to make learning more engaging and effective. The study investigated the use of the Rosetta Stone app as a medium for EFL students' speaking abilities. As for this study, qualitative descriptive methods are used. This study used Rosetta Stone application as a learning medium in 8th grade students of MTSN 6 Bulukumba with a focus on word stress and intonation. The data source in the study was MTSN 6th grade students of Bulukumba's 8th grade which numbered 22 students. Data in this study were obtained from observation sheets and interview guidelines. The results show that the use of this application is effective in improving students' pronunciation skills especially in students who have just reached the 8th grade, with the introduction of word stress tests, intonation, and well-managed audio and image learning media on the app arousing enthusiastic learning interest from students. Not only that, this app can also provide a positive factor in English learning in beginners because its features are designed to be interesting and accessible anytime and anywhere.